IL-17A expression by both T cells and non-T cells contribute to HSV-IL-2-induced CNS demyelination - Hirose, Satoshi; Wang, Shaohui; Jaggi, Ujjaldeep; Matundan, Harry H.; Kato, Mihoko; Song, Xue-Ying; Molesworth-Kenyon, Sara J.; Lausch, Robert N.; Ghiasi, Homayon (Frontiers in Immunology, 2023)
Previously we reported that a recombinant HSV-1 expressing murine IL-2 (HSV-IL-2) causes CNS demyelination in different strains of mice and in a T cell-dependent manner. Since TH17 cells have been implicated in CNS pathology, in the present study, we looked into the effects of IL-17A-/- and three of its receptors on HSV-IL-2-induced CNS demyelination. IL-17A-/- mice did not develop CNS demyelination, while IL-17RA-/-, IL-17RC-/-, IL-17RD-/- and IL-17RA-/-RC-/- mice developed CNS demyelination. Adoptive transfer of T cells from wild-type (WT) mice to IL-17A-/- mice or T cells from IL-17A-/- mice to Rag-/- mice induced CNS demyelination in infected mice. Adoptive T cell experiments suggest that both T cells and non-T cells expressing IL-17A contribute to HSV-IL-2-induced CNS demyelination with no difference in the severity of demyelination between the two groups of IL-17A producing cells. IL-6, IL-10, or TGFβ did not contribute to CNS demyelination in infected mice. Transcriptome analysis between IL-17A-/- brain and spinal cord of infected mice with and without T cell transfer from WT mice revealed that “neuron projection extension involved in neuron projection guidance” and “ensheathment of neurons” pathways were associated with CNS demyelination. Collectively, the results indicate the importance of IL-17A in CNS demyelination and the possible involvement of more than three of IL-17 receptors in CNS demyelination.